New 4-Pyridyl Nonaflates as Precursors for Push–Pull Solvatochromic Dyes - Domínguez, Moisés; Reissig, Hans-Ulrich (Synthesis, 2014)
2,6-Disubstituted 4-pyridyl nonaflates including methyl, phenyl, 2-thienyl and 2-furyl groups were prepared by cyclocondensation reactions of the appropriate β-ketoenamides. Palladium-catalyzed cross-couplings (Suzuki–Miyaura, Mizoroki–Heck and Sonogashira reactions) led to buildings blocks that are direct precursors for the envisioned synthesis of push–pull solvatochromic dyes.
Keywords: enamides; pyridines; cyclocondensations; nonaflates; cross-couplings